Manajemen Pembiayaan Kegiatan Ekstrakurikuler Terhadap Peningkatan Prestasi Siswa - H. Soro, Suharyanto; Rifandi, Ahmad; Ibrahim, Ace; Ramadhan, Rifky (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The problem faced by educational units is about financing management in order to improve student achievement at SMP Itikurih Hibarna. The limited development of extracurricular activities is caused by less than optimal financing management. To improve these deficiencies, effective and efficient financing management is needed. The purpose of this study is to describe and identify financing management for the implementation of extracurricular activities at SMP Itikurih Hibarna. This study uses a case study approach with a qualitative method. Data collection methods are carried out through observation, in-depth interviews, and documentation. The results of the study indicate that financing management of extracurricular activities can improve student achievement (marked by increased student participation, program variations, and quality of activity implementation). In other words, good financing management contributes directly to the success of developing student achievement through extracurricular activities.